2001
DOI: 10.1007/pl00010355
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Requirement Defects: An Experiment in Process Improvement

Abstract: Inadequate requirements cause many problems in software products. This paper reports on an experiment to reduce the number of requirement defects. We analysed the present defects in a real-life product and estimated the likely effect of 44 prevention techniques. We had hoped a novel combination of techniques would come up, but the best approach was quite well known, although new to the company: study the user tasks better, make early prototypes of the user interface, and test them for usability. This approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 15 publications
(12 reference statements)
0
57
0
Order By: Relevance
“…Validation is an official determination that a framework is acceptable with respect to a set of explicit standards for a specific purpose [11]. As for this research, an expert panel opinion validation is utilised as suggested by other researchers [12][13][14][15][16]. The expert validation is obtained using a questionnaire by means of a structured interview.…”
Section: Validations Of Frameworkmentioning
confidence: 99%
“…Validation is an official determination that a framework is acceptable with respect to a set of explicit standards for a specific purpose [11]. As for this research, an expert panel opinion validation is utilised as suggested by other researchers [12][13][14][15][16]. The expert validation is obtained using a questionnaire by means of a structured interview.…”
Section: Validations Of Frameworkmentioning
confidence: 99%
“…(Brodman and Johnson 1994;Hayes and Zubrow 1995;Sommerville and Sawyer 1997;Lauesen and Vinter 2001;Hall et al 2002a). We appreciate that the SW CMM is not a perfect model of software process assessment and improvement, as Paulk et al (1995) admit, "all models are wrong; some are useful.…”
Section: Reasons For Using the Sw Cmmmentioning
confidence: 99%
“…A criticism of the SW CMM is that it is too descriptive and does not provide sufficient examples and specific guidelines to help companies with their process improvement activities, e.g. (Lauesen and Vinter 2001;Potter and Sakry 2001). By taking key RE sub-processes and extending them into detailed guidelines the R-CMM features specific activities that in turn can be measured.…”
Section: Processes: the Substance Of The R-cmmmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauesen and Vinter, for example, looked at defect reports available a few months after a product's release. They found that about half of the defect reports involved requirements defects, with missing requirements being the most-frequent cause [6]. Requirements-related deficiencies were also found to be common causes of safety-critical anomalies during operations [8].…”
Section: Related Workmentioning
confidence: 99%